Obligate development of Blastocrithidia papi (Trypanosomatidae) in the Malpighian tubules of Pyrrhocoris apterus (Hemiptera) and coordination of host-parasite life cycles - Frolov, Alexander O; Malysheva, Marina N; Ganyukova, Anna I; Yurchenko, Vyacheslav; Kostygov, Alexei Y (PloS one, 2018)
Blastocrithidia papi is a unique trypanosomatid in that its life cycle is synchronized with that of its host, and includes an obligate stage of development in Malpighian tubules (MTs). This occurs in firebugs, which exited the winter diapause. In the short period, preceding the mating of overwintered insects, the flagellates penetrate MTs of the host, multiply attached to the epithelial surface with their flagella, and start forming cyst-like amastigotes (CLAs) in large agglomerates. By the moment of oviposition, a large number of CLAs are already available in the rectum. They are discharged on the eggs' surface with feces, used for transmission of bugs' symbiotic bacteria, which are compulsorily engulfed by the newly hatched nymphs along with the CLAs. The obligate development of B. papi in MTs is definitely linked to the life cycle synchronization. The absence of peristalsis allow the trypanosomatids to accumulate and form dense CLA-forming subpopulations, whereas the lack of peritrophic structures facilitates the extensive discharge of CLAs directly into the hindgut lumen. The massive release of CLAs associated with oviposition is indispensable for maximization of the infection efficiency at the most favorable time point.
Keywords: kladení vajíček; Life Cycle Stages; Hemiptera; stadia vývoje; Epithelial Cells; Feces; Malpighian Tubules; střeva; Host-Pathogen Interactions; Trypanosomatina; Animals; Intestines; epitelové buňky; feces; interakce hostitele a patogenu; zvířata; malpighické trubice; Oviposition